2002
DOI: 10.1053/jlts.2002.30882
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprophylaxis with basiliximab, a chimeric anti[ndash ]interleukin-2 receptor monoclonal antibody, in combination with azathioprine-containing triple therapy in liver transplant recipients

Abstract: Acute graft rejection remains a major problem among additional sequelae in liver transplant recipients. Basiliximab, a chimeric monoclonal antibody with high affinity for the CD25 chain of the interleukin-2 receptor, has significantly reduced the incidence of acute rejection episodes in renal transplant recipients. This single-arm, open-label, multicenter study investigated the efficacy and tolerability of basiliximab immunoprophylaxis in adult patients undergoing first elective liver transplantation. One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 28 publications
2
48
0
2
Order By: Relevance
“…Hintergrund sind das Nebenwirkungsprofil sowie der postulierte negative Effekt auf den Verlauf der HCV-Infektion. Die Induktionstherapie mit Anti-CD25-Antikörpern hat zur schnelleren Reduktion von Steroiden beigetragen und Rejektionsraten nicht erhöht, sondern sogar zu geringeren steroidrefraktären Rejektionsraten geführt [9,14,15,35]. Auch mit Kaninchen-Anti-Thymozytenglobulin (ATG) und Tacrolimus versus Tacrolimus, Mycophenolsäure und Steroiden konnte ein vergleichbares Über-leben, aber geringere Rejektionsraten der steroidfreien Gruppe gezeigt werden, wobei sogar die HCV-Rekurrenz geringer in der ATG-Gruppe erschien [13,15].…”
Section: Vermeidung Von Kortikosteroidenunclassified
“…Hintergrund sind das Nebenwirkungsprofil sowie der postulierte negative Effekt auf den Verlauf der HCV-Infektion. Die Induktionstherapie mit Anti-CD25-Antikörpern hat zur schnelleren Reduktion von Steroiden beigetragen und Rejektionsraten nicht erhöht, sondern sogar zu geringeren steroidrefraktären Rejektionsraten geführt [9,14,15,35]. Auch mit Kaninchen-Anti-Thymozytenglobulin (ATG) und Tacrolimus versus Tacrolimus, Mycophenolsäure und Steroiden konnte ein vergleichbares Über-leben, aber geringere Rejektionsraten der steroidfreien Gruppe gezeigt werden, wobei sogar die HCV-Rekurrenz geringer in der ATG-Gruppe erschien [13,15].…”
Section: Vermeidung Von Kortikosteroidenunclassified
“…Calmus et al 4 report excellent 1-year patient and graft survival rates of 90.1% and 88.1%, respectively, as well as no anaphylactic reaction or other major side effect related to the infusion of basiliximab. These investigators conclude that the addition of basiliximab resulted in a reduction in the number of rejection episodes compared with a historic control population, with no increased incidence of malignancies, infections, or other side effects.…”
mentioning
confidence: 99%
“…Calmus et al 4 report the results of a single-arm, open-label, multicenter trial of basiliximab in which 101 patients were administered basiliximab in conjunction with cyclosporine, azathioprine, and corticosteroids. They found an overall rejection rate of 22.8% at 6 months, with more rejection episodes in patients with hepatitis C (9 of 31 patients; 29.0%).…”
mentioning
confidence: 99%
“…In 2002, several studies demonstrated that two-dose basiliximab induction in liver transplant patients was well-tolerated and effective in reducing BPAR rates (35.1% basiliximab vs. 43.5% placebo at sixmonth follow up), although to a lesser extent in HCV-positive cohorts. [103][104][105] Lin et al further demonstrated that by allowing for delayed tacrolimus administration, basiliximab induction preserved renal function better than conventional therapy (renal insufficiency incidence of 26% vs. 67% at three-month follow up). 106 To minimize toxicity, steroid-withdrawal protocols have been actively tested in conjunction with basiliximab usage.…”
mentioning
confidence: 99%